La «maison de succession» à l’époque néo-assyrienne - Montero Fenollós, Juan-Luis (Gerión. Revista de Historia Antigua, 2006)
This paper is a study, through archaeological, iconographic and textual documentation, about an essential institution in the neo-assyrian monarchy succession system. This institution is the bīt ridûti or the «house of succession», which was the residence of “crown prince” in Assyria in the eighth and seventh centuries B.C.